China and Russia Energy Strategy Development: Arctic LNG - Steblyanskaya, Alina; Qingchao, Xu; Razmanova, Svetlana; Steblyanskiy, Nikolay; Denisov, Artem (International Journal of Energy Economics and Policy, 2021)
Nowadays, the LNG market is a derivative of the traditional gas market and has certain advantages over pipeline gas supplies. Many countries, including the Russian Federation, are trying to consolidate their positions in the relatively new and growing LNG market. In the paper, Sino-Russia Energy strategy perspectives until 2030 are being analyzed in detail. The authors analyze the Arctic LNG case as the most crucial for both countries' collaboration. The Arctic is considered as the new strategic frontier of China. China is a critical Arctic stakeholder as it is written in the newly released white paper China's Arctic Policy. The authors use Python 3.4. modeling for testing the influence of economic, social and environmental factors on Sino-Russia energy collaboration. The methodology consists of foresight analysis, including principal component isolation (further- PCA) method and SARIMA analysis. Research results show that the values of the components in Russia and China industries are drastically different. However, some components would be significantly developed due to Russia's existing trends by 2030. Indeed, it can be concluded that the dissimilarity between Russia and China' oil and gas industries would increase by 2030, as indicated by the first, second and fourth components. China's oil and gas industry has a stable trend for development. Keywords: Sino-Russia Energy Cooperation, Energy Strategy 2030, Innovation Strategy, Arctic LNG, Principal Component Isolation analysis JEL Classifications: F42, F43, F47, L51 DOI: https://doi.org/10.32479/ijeep.11316